Slip flow past slender pointed bodies - Stribling, C. B. (College of Aeronautics, 1963)
Using Oseen's approximation to linearise the Navier-Stokes equations, a solution to the problem of axisymmetric slip flow past slender bodies of revolution at zero incidence has been obtained, in a manner similar to that used by Laurmann in his paper on the slip flow past a flat plate(6). The drag coefficient has been evaluated for both incompressible and compressible flows, and this has been compared with normal boundary layer values. It is found that the skin friction drag is the dominant component of drag in the incompressible case and in the compressible case.